An Archaeological Evolution - South, Stanley; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
Stanley South has been a leading figure not only in histoical archaeology but also a leading figure in anthropological archaeology as well. His work (both past and present) has put him in the forefront of monumental changes in American archaeology in the last 40 years. His personal perserverance in field archaeology has also been an inspiration to new and burgeoning archaeologists and anthropologists. An Archaeological Evolution is a personal recounting of his life as it is played out among some of the most important debates and movements in archaeology starting in the 1960's up to the 21st century. This seminal volume will be of interest to archaeologists (both professional and academic), anthropologists, historians, and conservators in or studying the United States but also, wherever archaeology is taught and practiced.
The Formative Years -- Escaping the Groundhog Hole -- Appalachian Stories and After -- UNC Stories -- The Developmental Years -- Town Creek Stories -- SEAC Stories -- Brunswick Town Stories -- Digging Art and Life Stories -- Civil War Stories -- Tales from “A Loose Cannon” -- The Fluorescent Years -- Charles Towne Tales -- Politics and Potsherd Stories -- Ninety Six Stories -- “Loose” In South Carolina -- The Climactic Years -- Method and Theory Stories -- Spanish Santa Elena and French Charlesfort Tales -- Tales Beyond Santa Elena.
Keywords: Archaeology; Archaeology